European Union: Collective bargaining and internal flexibility during the Great Recession - Santos Ruesga Benito; María Isabel Heredero de Pablos; Julimar Da Silva Bichara; Laura Pérez Ortiz; Ana Apaolaza Vi\~nas; Sandro Eduardo Monsueto (Economics: The Open-Access, Open-Assessment E-Journal, 2020)
The paper's main objective is to analyze the collective bargaining response in terms of internal flexibility during the Great Recession (GR) in five EU countries (Spain, Germany, France, Italy, United Kingdom), and three economic sectors (industry, commerce and hospitality, and financial services and real estate), at the establishment level (ECS2013 database). The theoretical framework used is linked to the varieties of unionism and to the debate on the tendency towards the international homogenization or heterogenization of collective bargaining between the European Union countries. Using a descriptive statistical analysis and a probit model, this paper presents new evidences. However, the responses were heterogeneous between countries and sectors, the use of internal functional flexibility has been more intense than the numerical and salary internal flexibility. Moreover, it is related to the intensity of GR. These results, in general, while requiring a more detailed analysis of the effects of the GR on internal flexibility in the EU countries, contribute to introducing a new perspective in the socioeconomic literature about the collective bargaining and internal flexibility.
Keywords: J51; 330; European Union; collective bargaining; internal flexibility; Great Recession; establishment level